The consequences of cohesin mutations in myeloid malignancies - Bhattacharya, Shubhra Ashish; Dias, Eve; Nieto-Aliseda, Andrea; Buschbeck, Marcus (Frontiers in Molecular Biosciences, 2023)
Recurrent somatic mutations in the genes encoding the chromatin-regulatory cohesin complex and its modulators occur in a wide range of human malignancies including a high frequency in myeloid neoplasms. The cohesin complex has a ring-like structure which can enclose two strands of DNA. A first function for the complex was described in sister chromatid cohesion during metaphase avoiding defects in chromosome segregation. Later studies identified additional functions of the cohesin complex functions in DNA replication, DNA damage response, 3D genome organisation, and transcriptional regulation through chromatin looping. In this review, we will focus on STAG2 which is the most frequently mutated cohesin subunit in myeloid malignancies. STAG2 loss of function mutations are not associated with chromosomal aneuploidies or genomic instability. We hypothesize that this points to changes in gene expression as disease-promoting mechanism and summarize the current state of knowledge on affected genes and pathways. Finally, we discuss potential strategies for targeting cohesion-deficient disease cells.